2020
DOI: 10.3390/nano10122483
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Near-Perfect Spectrum-Selective Mirror Based on Photonic Structures for Passive Cooling of Silicon Solar Cells

Abstract: When exposed to sunlight, crystalline silicon solar cells (CSSC) will not only generate electric energy but are also heated by solar radiation. Such a self-heating effect makes the working temperature of CSSC 20–40 °C higher than that of the ambient temperature, which degrades their efficiency and reliability. The elevated operating temperatures of CSSC are mainly derived from absorbing photons that cannot be converted to electrons. Therefore, it is important to prevent CSSC from absorbing useless solar light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Zhu et al [20] integrated RC with a bare crystalline Si PV panel, demonstrating that the PV panel's temperature could be reduced by 18.3 °C at 1 sun. Also, based on a crystalline Si cell, a PV system integrated with SS and RC was proposed by Gao et al, [21] and the experimental results indicated that the panel's temperature could be reduced by 23.2 °C when the wind speed was 3 m s −1 and by 68.1 °C when there was no wind. Wang et al [22] conducted multiple simulations and experiments to investigate the impact of radiative cooling on solar cells, they found RC performance varied significantly with changes in wind speed, heat load, and design, the temperature drop of 36 °C was observed in a sealed chamber relative to a system without RC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [20] integrated RC with a bare crystalline Si PV panel, demonstrating that the PV panel's temperature could be reduced by 18.3 °C at 1 sun. Also, based on a crystalline Si cell, a PV system integrated with SS and RC was proposed by Gao et al, [21] and the experimental results indicated that the panel's temperature could be reduced by 23.2 °C when the wind speed was 3 m s −1 and by 68.1 °C when there was no wind. Wang et al [22] conducted multiple simulations and experiments to investigate the impact of radiative cooling on solar cells, they found RC performance varied significantly with changes in wind speed, heat load, and design, the temperature drop of 36 °C was observed in a sealed chamber relative to a system without RC.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [ 20 ] integrated RC with a bare crystalline Si PV panel, demonstrating that the PV panel's temperature could be reduced by 18.3 °C at 1 sun. Also, based on a crystalline Si cell, a PV system integrated with SS and RC was proposed by Gao et al, [ 21 ] and the experimental results indicated that the panel's temperature could be reduced by 23.2 °C when the wind speed was 3 m s −1 and by 68.1 °C when there was no wind. Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, several different materials and methods have been explored to cool solar cells with PRC: multilayers, , 2D structures, a combination of a multilayer and 2D structures, , or an effective medium approach. Table lists the calculated (italic) or fabricated (bold) material systems of a few notable works, and their reported temperature reduction: calculated values are in italic, measured values in bold font. To enable comparison of the achieved temperature reductions, it is important to specify the reference material system.…”
mentioning
confidence: 99%
“…A solar cell absorbs light with photon energy larger than the bandgap energy, including visible wavelengths. Over the past years, several different materials and methods have been explored to cool solar cells with PRC: multilayers, 15,16 2D structures, 17−23 a combination of a multilayer and 2D structures, 24,25 or an effective medium approach. 26−28 Table 1 lists the calculated (italic) or fabricated (bold) material systems of a few notable works, and their reported temperature reduction: calculated values are in italic, measured values in bold font.…”
mentioning
confidence: 99%